2012
DOI: 10.1177/0957650912455386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tip clearance on impeller discharge flow and vaneless diffuser performance of a centrifugal compressor

Abstract: To see the tip clearance effect on a centrifugal compressor, time-resolved flow measurements are carried out at the discharge of a centrifugal compressor impeller with a diameter of 280 mm. The impeller is 30 back swept and is operated at a blade tip speed of 260 m/s, which is a rather high speed for measuring time-resolved flow. Six levels of tip clearance ratio ranging from 0.06 to 0.21 were tested. A fast response aerodynamic probe equipped with a single pressure sensor is used for the flow measurements. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…As already found by Hong and Abhari (2012), the tip gap reduction has a positive outcome on the impeller efficiency (total-to-total: 95.0% for REF, 95.8% for CL02 and 96.5% for CL00), while its influence seems to be harmful for the vaneless diffuser performance. In fact, the radial velocity contours in Fig.…”
Section: Ref Casesupporting
confidence: 72%
See 1 more Smart Citation
“…As already found by Hong and Abhari (2012), the tip gap reduction has a positive outcome on the impeller efficiency (total-to-total: 95.0% for REF, 95.8% for CL02 and 96.5% for CL00), while its influence seems to be harmful for the vaneless diffuser performance. In fact, the radial velocity contours in Fig.…”
Section: Ref Casesupporting
confidence: 72%
“…This work considers primarily the concepts about lean widely discussed for axial turbomachines (see for example Denton et al, 1999;D'Ippolito et al, 2011;Rosic et al, 2012) and less frequently for radial machines (Van den Braembussche, 2006;He and Zheng, 2016). As for the tip clearance, among the works found in literature Baines and Whitfield (1990), Brasz (1998), Baskharone (2006, Hong and Abhari (2012) are brought to the readers' attention. To take into account for this parameter in the 1D design process, the Daily&Nece correlation is often applied.…”
Section: Introductionmentioning
confidence: 99%
“…The tip leakage flow (TLF) has detrimental effects on compressor performance as reported by many existing experimental and numerical studies. The effects of TLF on the compressor performance can be classified into two aspects: First, the TLF would reduce the pressure rise and efficiency, which was related to the tip clearance size 1 and rotating speed 2 ; Second, the TLF would threat the safety and reliable operation of the compressors. When the mainflow/TLF interface approaches to the blade leading edge, the “spike” stall is triggered in axial rotor.…”
Section: Introductionmentioning
confidence: 99%
“…Their results show that better flow uniformity at the diffuser exit by the converging walls. The effect of tip clearance on impeller discharge flow and vaneless diffuser was investigated by Hong et al 15 The authors concluded that increasing the tip clearance reduces total pressure loss in the diffuser while increasing impeller loss. The authors also discovered that increasing tip clearance reduces the matching constant and skin friction coefficient.…”
Section: Introductionmentioning
confidence: 99%